Academic Self-Efficacy and Math Learning in Sidoarjo's High School Elementary Students: Hubungan Antara Keyakinan Diri Akademik dan Hasil Belajar Matematika pada Siswa Sekolah Dasar Tingkat Menengah di Sidoarjo - Fathu Rahman; Widyastuti Widyastuti (Academia Open, 2023)
This study aimed to investigate the relationship between academic self-efficacy and mathematics learning outcomes among upper-grade students in elementary schools in Sidoarjo. The participants included 185 students from the Prohibition State Elementary School and MI Muhammadiyah 2 Kedungbanteng, ranging from fourth to fifth grade. The study employed an academic self-efficacy scale and utilized mathematics learning outcomes obtained from student report cards. Data analysis was conducted using saturated sampling analysis, revealing a correlation coefficient of 0.135 (p=0.033). The findings indicated a moderate level of academic self-efficacy in 43% of students, high academic self-efficacy in 17%, and very high academic self-efficacy in 9%. Additionally, the R-square results demonstrated that academic self-efficacy accounted for 1.8% of the variance in mathematics learning outcomes, suggesting that other factors also contribute to students' performance. These findings highlight the importance of considering academic self-efficacy and other influential factors in enhancing mathematics learning outcomes among elementary school students. Highlights: The study examines the relationship between academic self-efficacy and mathematics learning outcomes in upper-grade students from elementary schools in Sidoarjo. A total of 185 participants from Prohibition State Elementary School and MI Muhammadiyah 2 Kedungbanteng were involved in the study. The findings suggest that academic self-efficacy accounts for 1.8% of the variance in mathematics learning outcomes, indicating the presence of other influencing factors. Keywords: academic self-efficacy, math learning outcomes, upper-grade students, elementary school.